Structural geological mapping in Simpang Pulai to Pos Selim, Malaysia utilising satellite imagery - Ramli, Mohammad Firuz; Yusof, N.; Mohd Shafri, Helmi Zulhaidi; Misman, Muhamad Afizzul; Juahir, Hafizan; Yusoff, Mohd Kamil (2008)
Remote sensing data have becoming an improtant source of structural geological information. Integration of multispectral and radar imagery, with the digital elevation model may improve the structural interpretation. The main objective of this study is to utilise the radar imagery for lineament interpretation which probably represent the main joints or faults along the presently Simpang Pulai to Pos Selim highway. The Landsat was chosen because during the image capture, the highway stretch is still not been build, thus the interpretation of the lineamnet will not be influenced by the highway alignment. The resultant lineament will be compared to the previously interpreted lineaments in the study area using Landsat TM.